UNLOCKING FINANCIAL PERFORMANCE: A SIMULTANEOUS EQUATION ANALYSIS OF INDONESIA'S TOP 10 ISLAMIC BANKS - Mamay Komarudin (Yayasan Education and Social Center, 2026)
Purpose This investigation explores how various factors simultaneously shape financial outcomes in Indonesia's ten largest Islamic banking institutions through block-recursive simultaneous equation modeling, specifically tackling endogeneity complications embedded within performance measurement systems. Design/methodology/approach Drawing on quarterly panel observations spanning 2020-2024 from Indonesia's ten largest Islamic banks, we implement Three-Stage Least Squares estimation techniques to examine three interrelated subsystems: earnings performance measured through ROA, cost management effectiveness captured by BOPO, and portfolio quality indicated by NPF. Our simultaneous framework reveals reciprocal linkages and feedback mechanisms operating among these endogenous constructs. Findings Empirical estimation uncovers substantial simultaneous linkages connecting performance dimensions. Cost inefficiency undermines profitability (β₁ = -0.0847, p<0.01), while portfolio deterioration exerts negative consequences on earnings (β₂ = -0.2341, p<0.01). Reciprocal influences demonstrate that enhanced profitability drives cost efficiency gains (α₁ = -0.3156, p<0.01) and strengthens portfolio quality (γ₁ = -0.1823, p<0.05). Institutional scale and capital strength function as pivotal performance drivers, whereas macroeconomic forces exhibit differential impacts across analytical blocks. Research limitations/implications Our investigation concentrates on ten leading institutions, potentially constraining applicability to smaller market participants. Subsequent investigations might incorporate nonlinear specifications and expanded risk measurement frameworks. Practical implications Evidence suggests Islamic banking institutions must emphasize cost efficiency enhancement to establish sustainable earnings trajectories. Supervisory authorities need to recognize interconnected performance dynamics when constructing prudential oversight mechanisms for Islamic financial institutions. Originality/value This work enriches Islamic banking scholarship by deploying simultaneous equation techniques to capture intricate interdependencies infrequently examined in prior investigations, yielding thorough perspectives on Indonesian Islamic banking operational dynamics.